Teachers’ knowledge, skill and self importance in the implementation of English literacy - Mustafa Che Omar, Norfazila Ghazali,; Saputra, Jumadil (Opción, 2019)
This study was conducted to identify the skills among English teachers in teaching Literacy pupils in primary school. In this vein, CEFR is used to measure the standard level of language proficiency among pupils. There are various problems identified at the beginning of the introduction of this program. To achieve the objectives, this study uses the document analysis through the review of the literature. Based on the results of the analysis, this study found that teachers faced the difficulties in implementing the new programs and facing the problematic pupils at the same time.